Drug awareness roadshow - Daily Express, (KK) (Daily Express (KK), 2017)
KUDAT: Drugs is the country's No. 1 enemy that must be addressed immediately for it could destroy the future of the younger generation, said Minister of Special Tasks Datuk Teo Chee Kang.